2021
DOI: 10.3389/fneur.2021.768718
|View full text |Cite
|
Sign up to set email alerts
|

Test Batteries and the Diagnostic Algorithm for Chronic Vestibular Syndromes

Abstract: Objective: To develop a diagnostic algorithm for chronic vestibular syndromes by determining significant items that differ among diagnoses.Methods: Two hundred thirty-one patients with chronic vestibular syndromes lasting for >3 months were included. Full vestibular tests and questionnaire surveys were performed: bithermal caloric test, cervical and ocular vestibular-evoked myogenic potential assessment, video head impulse test (vHIT), posturography, rotatory chair test, dizziness handicap inventory, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…Patients with PPPD had precipitating vestibular conditions, such as an acute attack of peripheral vestibular vertigo, Meniere's disease, and vestibular neuritis; however, CP% was within normal range and remained significantly lower than that of patients with UVH. Nonetheless, the DHI scores and NPQ scores of patients with PPPD were significantly higher than those of patients with UVH, indicating that patients with PPPD had more severe subjective handicaps, even with normal vestibular function; this is consistent with a previous report (Kitazawa et al, 2021). On the NPQ subscale, the PPPD group scored significantly higher than the UVH group on visual stimulation, indicating that visual exacerbation is specifically observed in the PPPD group, as in previous reports (Yagi et al, 2019).…”
Section: Clinical and Demographic Characteristics Of Persistent Postu...supporting
confidence: 90%
“…Patients with PPPD had precipitating vestibular conditions, such as an acute attack of peripheral vestibular vertigo, Meniere's disease, and vestibular neuritis; however, CP% was within normal range and remained significantly lower than that of patients with UVH. Nonetheless, the DHI scores and NPQ scores of patients with PPPD were significantly higher than those of patients with UVH, indicating that patients with PPPD had more severe subjective handicaps, even with normal vestibular function; this is consistent with a previous report (Kitazawa et al, 2021). On the NPQ subscale, the PPPD group scored significantly higher than the UVH group on visual stimulation, indicating that visual exacerbation is specifically observed in the PPPD group, as in previous reports (Yagi et al, 2019).…”
Section: Clinical and Demographic Characteristics Of Persistent Postu...supporting
confidence: 90%
“…The reason for this observation could be the punctuation and the composition of the “control” group to compare, since our control group has more cases of migraine and vestibular migraine that have usually presented a high NPQ score and its subscales in a similar way than PPPD subjects. Nonetheless, Kitazawa et al noted that the NPQ is the most useful tool for the diagnosis of PPPD when compared with the video head impulse test, posturography, rotatory chair test, the DHI, bithermal caloric test and cervical and ocular vestibular-evoked myogenic potential assessment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, since the publication of the scale in 2019, several studies have used the NPQ in the assessment of PPPD in Japanese patients. In addition to the study of Kitazawa [ 30 ] previously mentioned, Yamaguchi et al used the NPQ to assess the effects of a treatment based on virtual reality in participants with PPPD, determining that participants improved their symptoms [ 31 ]. Similarly, Miwa and Kanemaru observed 15.5 points of improvement in the NPQ using traditional medicine in PPPD patients [ 32 ], which is greater than the MDC obtained by our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have revealed the association of vestibular function in PPPD with preceding balance disorders. Some previous articles have focused on the vestibular function in PPPD [ 5 , 21 ], including a few which have suggested specific laboratory findings for this disease [ 22 , 23 ]. For example, the functional head impulse test with optokinetic stimulation provoked more reading errors in patients with PPPD than in controls [ 22 ].…”
Section: Discussionmentioning
confidence: 99%